IMPLEMENTASI PENGENDALIAN MUTU PENDIDIKAN DI MADRASAH - Sholihah Fatimatuz Zahro; Romi Faslah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted to examine the implementation of quality control in madrasahs in order to improve the overall quality assurance of education. This research employed a library research method by searching for literature related to the chosen theme. The collected literature was then compiled and analyzed. The findings show that the implementation of quality control in madrasahs involves three essential aspects: input, process, and output. It is expected that research can contribute to improving the quality of education in Indonesia.